PROMISING TRENDS OF INTERMUNICIPAL COOPERATION FOR THE PURPOSE OF EFFECTIVE USE OF INVESTMENT POTENTIAL OF VOLOGDA REGIONS - M. Andreeva (Вестник университета)
The investment potential of the territory of the Vologda Region makes it possible to implement investment projects in various economic spheres. The article explains expediency of using such an instrument as intermunicipal cooperation for solving the problem. Long-term cooperation areas of the Vologda region are defined.